Peran Pustakawan dalam Pembelajaran Literasi Informasi Mahasiswa Universitas Islam Negeri Imam Bonjol - Kamil Harahap, Ilham; Zaindzikra, Dillah (UIN Imam Bonjol Padang, 2022)
This article is entitled “The Role of Librarians in Learning Information Literacy for UIN Imam Bonjol Padang Students” The background in article writing is based on the current situation where university libraries rarely teach information literacy to students. The purpose of this study was to describe the role of librarians in learning information literacy for UIN Imam Bonjol Padang students. This research uses descriptive qualitative method with a case study approach. The data used are primary data and secondary data, with interview and observation data collection methods. The informants selected in this study were four people consisting of three students and one librarian. The selection of informants in this study was taken using a purposive sampling technique. Analysis of the data used using Miles & Huberman's data analysis model. Applying the aspects of Wheeler and Pamela McKinney about the role of librarians, the results of this study indicate that librarians have a role as learning support, librarian who teaches, or information literacy trainer.